1996
DOI: 10.1115/1.2836683
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer Enhancement Within a Turbine Blade Cooling Passage Using Ribs and Combinations of Ribs With Film Cooling Holes

Abstract: A transient heat transfer method using liquid crystals has been applied to a scale model of a turbine rotor blade passage. Detailed contours of local heat transfer coefficient are presented for the passage in which the heat transfer to one wall was enhanced first by ribs and then with ribs combined with holes. The hole geometry and experimental dimensionless flow rates were representative of those occurring at the entrance to engine film cooling holes. The results for the ribbed passage are compared to establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Ekkad et al [23] used a twopass channel with 20 holes in both the upstream and downstream leg, and a SR=0. 8. It found that the extraction did not modify the area-averaged 0 / Nu Nu ratios.…”
Section: Influence Of Extractionmentioning
confidence: 96%
See 2 more Smart Citations
“…Ekkad et al [23] used a twopass channel with 20 holes in both the upstream and downstream leg, and a SR=0. 8. It found that the extraction did not modify the area-averaged 0 / Nu Nu ratios.…”
Section: Influence Of Extractionmentioning
confidence: 96%
“…It found extraction to have appreciable effects on the full surface heat transfer distribution. Shen et al [8] used a single-pass channel with five holes and with SR=1.85 to 5.07. It showed that the extraction raised the averaged heat transfer value from the 0% extraction ribbed wall by about 25%, independently of the suction ratio.…”
Section: Influence Of Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the required large channel width-to-height ratios in the range of 6-10 for present application, the flow structures and heat transfer characteristics in a twin-blow narrow channel are considerably modified from the conventional single-blow scenarios. Although the heat transfer enhancement using surface ribs has been a subject of much fundamental research over the last two decades [1][2][3][4][5][6][7][8][9][10][11], no previously published work is available for the ribroughened channel with twin blow entrances. In this respect, the absence of research efforts and the need for electronic cooling in a notebook PC have motivated the present study.…”
Section: Introductionmentioning
confidence: 99%
“…Theses rib-roughened channels take varying cross-sectional shapes with a wide range of rib geometries typical of rib-angle 30 • -90 • , rib-height 0.0625-0.15 of channel-hydraulic-diameter and rib-pitch 8-30 of rib-height that are formulated as continuous, broken and V shaped with inline, staggered and criss-cross arrangements [1][2][3][4][5][6][7][8][9][10][11]. The studies of heat transfer in a rib-roughened narrow channel results in the large channel width-to-height ratio.…”
Section: Introductionmentioning
confidence: 99%